Queen of air and darkness - Clare, Cassandra (New York : Margaret K. McElderry Books, 2018)
Innocent blood has been spilled on the steps of the Council Hall, the sacred stronghold of the Shadowhunters. In the wake of the tragic death of Livia Blackthorn, the Clave teeters on the brink of civil war. One fragment of the Blackthorn family flees to Los Angeles, seeking to discover the source of the disease that is destroying the race of warlocks. Meanwhile, Julian and Emma take desperate measures to put their forbidden love aside and undertake a perilous mission to Faerie to retrieve the Black Volume of the Dead. What they find in the Courts is a secret that may tear the Shadow World asunder and open a dark path into a future they could never have imagined. Caught in a race against time, Emma and Julian must save the world of Shadowhunters before the deadly power of the parabatai curse destroys them and everyone they love.--
Keywords: Demonology -- Fiction; Magic -- Fiction; Los Angeles (Calif.) -- Fiction; Paranormal fiction; Fantasy fiction